A new perspective: Fat tissue and adipokines in rheumatic heart valves. Issue 12 (24th November 2022) - Xie, Ting; Wu, Danna; Zhang, Jie; Qiao, Ping; Chen, Xuan; Liu, Debin; Xiang, Mei; Li, Haitao; Cai, Xingjiu; Lin, Zhichuan; Yang, Wenkai; Chen, Xinzhong; et al.
Abstract: Objective: To observe fat tissue and the expression of adipokines in rheumatic heart valves and explore the possible role of fat tissue and adipokines in the pathology of rheumatic heart disease (RHD). Methods: In this retrospective study, a total of 29 patients who received mitral valve replacement surgery were included. The study group consisted of 25 patients with RHD while the control group consisted of 4 patients with secondary mitral insufficiency caused by coronary heart disease (CAD). The clinical data of the patients including medical history, age, body mass index (BMI), fasting blood glucose (FBG), total triglycerides (TG), total cholesterol (TC), high‐density lipoprotein‐cholesterol (HDL‐C), low‐density lipoprotein‐cholesterol (LDL‐C), apolipoprotein(a) [apo(a)], apolipoprotein(b) [apo(b)] were collected and compared. Cardiac ultrasonography was used to assess valve conditions before surgery. The removed valves were collected. The hematoxylin–eosin (HE) staining, oil‐red O staining, and Masson's trichrome staining were adopted to evaluate the histological changes in the mitral valve. Immunohistochemical (IMC) staining was performed to evaluate the expression of adiponectin, leptin, and chemerin. Results: There was no significant difference in general information and blood lipid levels between the two groups (all p > .05). Preoperative ultrasonography showed adipose tissue in the mitral valve of RHD patients. In the study group, rheumatic mitral valve samples showed thickening, adherence at the junction of the leaflets, calcification, and yellowish or fat mass by naked observation. The HE staining showed that there was calcification, inflammatory cell infiltration, fibrous tissue arranged disorder, and neovascularization. The oil‐red O staining suggested fatty infiltration. Masson's trichrome staining suggested disorderly arrangement of collagen fiber and elastic fiber in rheumatic lesions, and the lesions were dominated by collagen fiber hyperplasia and less elastic fiber hyperplasia. The results of IMC indicated that chemerin was not expressed in valves of the control group. Most of the valve samples from the study group also did not show leptin and the leptin was seen in only a few rheumatic mitral valves with vascular hyperplasia. Adiponectin was not found in the valves of the study group and the control group. Conclusion: Adipose tissue in the rheumatic mitral valve could be observed by ultrasound. The fat mass and adipokines existed in rheumatic mitral valves, the adipocytokine chemerin is involved in the progression of the pathology in RHD.